2008
DOI: 10.1111/j.1462-2920.2007.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diversity in the oxygen minimum zone of the eastern tropical South Pacific

Abstract: The structure and diversity of bacterial communities associated with the oxygen minimum zone (OMZ) of the eastern tropical South Pacific was studied through phylogenetic analysis. Clone libraries of 16S rRNA gene fragments were constructed using environmental DNA collected from the OMZ (60 m and 200 m), the sea surface (10 m), and the deep oxycline (450 m). At the class level, the majority of sequences affiliated to the gamma- (53.7%) and alpha-Proteobacteria (19.7%), and to the Bacteroidetes (11.2%). A vertic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
199
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(247 citation statements)
references
References 84 publications
42
199
2
4
Order By: Relevance
“…SUP05 is abundant in oxic/anoxic interfacial environments such as deep-sea hydrothermal plumes (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010), oxygen minimum zones (Stevens and Ulloa, 2008;Lavik et al, 2009;Walsh et al, 2009;Canfield et al, 2010) and symbioses with deep-sea bivalves (Newton et al, 2007). Our data set supports previous genomic studies that showed that members of this group are chemolithoautotrophic, obtaining energy by coupling sulfur oxidation to reduction of nitrate and/or oxygen (Newton et al, 2007;Walsh et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…SUP05 is abundant in oxic/anoxic interfacial environments such as deep-sea hydrothermal plumes (Sunamura et al, 2004;Dick and Tebo, 2010;German et al, 2010), oxygen minimum zones (Stevens and Ulloa, 2008;Lavik et al, 2009;Walsh et al, 2009;Canfield et al, 2010) and symbioses with deep-sea bivalves (Newton et al, 2007). Our data set supports previous genomic studies that showed that members of this group are chemolithoautotrophic, obtaining energy by coupling sulfur oxidation to reduction of nitrate and/or oxygen (Newton et al, 2007;Walsh et al, 2009).…”
Section: Discussionsupporting
confidence: 80%
“…The Chloroflexi were represented by 38 OTUs, all of them falling in the yet--uncultivated phylogenetic clade SAR202. These Bacteria are common in meso--and bathypelagic ocean waters (Morris et al 2004;Schattenhofer et al 2009) but also in oxygen minimum zones (Stevens & Ulloa 2008). The 30 Gammaproteobacterial OTUs recovered from sediments at the control site were related to known bacterial genera in deep--sea sediments such as Pseudomonas, Pseudolateromonas, Psychrobacter and Aliivibrio.…”
Section: Methodsmentioning
confidence: 96%
“…The most abundant group represented only 10% of the Gammaproteobacteria sequences and belonged to an uncultured cluster, previously named Arctic96BD-19 (Bano and Hollibaugh, 2002) or the GSO cluster (Lavik et al, 2009), containing a chemolithotrophic sulfide-oxidizer bacteria. The second most abundant group of Gammaproteobacteria sequences belonged to the ZD0417 cluster (Stevens and Ulloa, 2008) (Supplementary Figure S6). Other Gammaproteobacteria belonged to orders Oceanospirillales, Alteromonadales and Thiotrichales.…”
Section: Biogeography Of Bacteria In the Deep Arctic Ocean Pe Galand mentioning
confidence: 99%